Practices, patients and (im)perfect data - feasibility of a randomised controlled clinical drug trial in German general practices - Hummers-Pradier Eva (Trials, 2011)
Abstract Background Randomised controlled clinical (drug) trials supply high quality evidence for therapeutic strategies in primary care. Until now, experience with drug trials in German general practice has been sparse. In 2007/2008, the authors conducted an investigator-initiated, non-commercial, double-blind, randomised controlled pilot trial (HWI-01) to assess the clinical equivalence of ibuprofen and ciprofloxacin in the treatment of uncomplicated urinary tract infection (UTI). Here, we report the feasibility of this trial in German general practices and the implementation of Good Clinical Practice (GCP) standards as defined by the International Conference on Harmonisation (ICH) in mainly inexperienced general practices. Methods This report is based on the experience of the HWI-01 study conducted in 29 German general practices. Feasibility was defined by 1) successful practice recruitment, 2) sufficient patient recruitment, 3) complete and accurate data collection and 4) appropriate protection of patient safety. Results The final practice recruitment rate was 18%. In these practices, 79 of 195 screened UTI patients were enrolled. Recruitment differed strongly between practices (range 0-12, mean 2.8 patients per practice) and was below the recruitment goal of approximately 100 patients. As anticipated, practice nurses became the key figures in the screening und recruitment of patients. Clinical trial demands, in particular for completing symptom questionnaires, documentation of source data and reporting of adverse events, did not agree well with GPs' documentation habits and required support from study nurses. In many cases, GPs and practice staff seemed to be overwhelmed by the amount of information and regulations. No sudden unexpected serious adverse reactions (SUSARs) were observed during the trial. Conclusions To enable drug trials in general practice, it is necessary to adapt the setup of clinical research infrastructure to the needs of GPs and their practice staff. Risk adaption of clinical trial regulations is necessary to facilitate non-commercial comparative effectiveness trials in primary health care. Trial Registration Trial registration number: ISRCTN00470468